(untitled) (Research, Society and Development, 2022)
This study analyzes the convergence of governance and planning at the intergovernmental level, based on the public policy approach for early childhood, called “Happy Child Program”. The method is qualitative, employing content analysis supported by the ATLAS.ti software. An attempt was made to analyze the implementation of a specific public policy, having as object of analysis the Multiannual Plans of the Federal Government and eleven municipalities that joined the Program in 2020. The results showed plans and practices that were mostly distant from a strategic perspective, as well as incipient governance mechanisms, predominantly oriented towards compliance with legal formalism. The practices identified in local governments, although still incipient, can reference new studies and similar practices in other municipalities. From a theoretical point of view, it presents the debate about multilevel governance and its interface with government strategic planning, both relevant to the development of mechanisms for coordinating public policies.